Adsorptive removal of toxic methyl orange textile dye from aqueous solutions using polypyrrole/graphitic carbon nitride composite - Gazdagli, Irem; Isik, Birol; Ugraskan, Volkan (TAYLOR & FRANCIS INC, 2026)
Graphitic carbon nitride (g-C3N4) has grown in popularity in adsorption along with various applications due to its ease of manufacture from sustainable sources, high surface area, and nitrogen-rich structure. Similarly, polypyrrole (PPy), a conductive polymer, has been one of the most investigated adsorbents in recent years due to its distinct characteristics. This study investigated the influence of combining these two promising components on adsorption performance for the removal of toxic methyl orange (MO) dye from aqueous solutions for the first time. For this purpose, PPy/g-C3N4 composites were prepared at different ratios of 10, 20, and 30 wt%. The qm was calculated as 38.26 mg/g from Langmuir and 37.96 mg/g from Sips for PPy/g-C3N4/30 at 298 K. The effect of salt concentration on the adsorption process was conducted using NaCl, NaNO3, Na2SO4, and CaCl2. The Delta Ho value for the PPy/g-C3N4/30 was 16.86 kJ/mol, indicating that the process was endothermic. The Delta Go value was found to be -29.67 kJ/mol at 298 K, indicating that the adsorption was spontaneous. The removal percentages for tap, drinking, and distilled water were 92.8, 95.0, and 95.9%, respectively. From the reusability studies, it was seen that the adsorbents can be used effectively repeatedly up to 6 cycles.
Keywords: Adsorption; methyl orange; polypyrrole; BLUE-DYE; PHOTODEGRADATION; FABRICATION; ISOTHERM; Chemistry; Science & Technology - Other Topics; Materials Science; Physics